New advances in mechanism and machine science : proceedings of the 12th IFToMM International Symposium on Science of Mechanisms and Machines (SYROM 2017) /: proceedings of the 12th IFToMM International Symposium on Science of Mechanisms and Machines (SYROM 2017). (2018) - Unknown
No abstract available